International relations theory of war - Israeli, Ofer, 1968- (Praeger security international (Series), 2019)
"This book tries to answer two key questions. The first is why certain periods are more prone to war than others. The other is why certain wars that involve polar powers end with their territorial expansion whereas other wars end in their contraction or maintaining their territorial status. In conclusion, it is asked whether the polarity of the system affects these two outcomes, and if so, how"--